PELAKSANAAN PEMBELAJARAN BAHASA INGGRIS DI SEKOLAH DASAR KOTA PADANG - Radjab, Desmawati; Syarif, Hermawati (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2009)
This article discusses and interpretes the findings of the study of the implementation of English instruction at Elementary Schools of Padang City. Through observation, questionnaire, informal interview, and documentation, the data were collected from the sample of state schools which offer English as the local subject. Using descriptive analysis technique, it was found that the implementation of the English instructional strategies did not truly follow the directions designed for the elementary school students for the teachers did not have definitive curriculum. Thus, the instruction was not much in a good track, that is (1) oral language skills tended to be ignored; (2) the instruction for three grades of the students (3, 4, and 5) was seen overlapped for they used the same book as the only source of the teaching materials; (3) the instructional assessment was conducted in all kinds, such as process evaluation, port-folio, formative and summative test. However, it was mostly on the written form, different from the objective of English learning at the elementary schools; and (4) there were problems faced in offering the subject, namely, the teachers were not fully given the opportunity to improve their English, and the status of English as local subject makes the subject ignored by the headmasters of schools.Â